Possibilities of Increasing Investment Attractiveness in Attracting Foreign Investments to the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reflects the results of a study conducted to determine the possibilities of increasing the investment attractiveness of the regions of the Republic of Uzbekistan. In the first part of the study, the scientific and theoretical foundations for increasing the attractiveness of the investment environment were studied, including the content of such closely related categories. The second part of the article examines areas for increasing the efficiency of investment projects in the regions, including an analysis of investment projects in the industrial zones in Uzbekistan and the possibility of using financial incentives to increase investment attractiveness.